2014
DOI: 10.1155/2014/253067
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Growth Patterns and Body Composition in C57Bl/6J Mice Using Dual Energy X-Ray Absorptiometry

Abstract: The normal growth pattern of female C57BL/6J mice, from 5 to 30 weeks of age, has been investigated in a longitudinal study. Weight, body surface area (BS), and body mass index (BMI) were evaluated in forty mice. Lean mass and fat mass, bone mineral content (BMC), and bone mineral density (BMD) were monitored by dual energy X-ray absorptiometry (DEXA). Weight and BS increased linearly (16.15 ± 0.64–27.64 ± 1.42 g; 51.13 ± 0.74–79.57 ± 2.15 cm2, P < 0.01), more markedly from 5 to 9 weeks of age (P < 0.001). BMD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
59
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 44 publications
7
59
1
Order By: Relevance
“…We compared theFgf13 +/2 mice's daily EE (previously corrected by ANCOVA for LBM, with that of WT mice and converted the deficit to grams by dividing by the caloric content of fat to obtain a predicted fat gain per day. We used the caloric content of fat because of the observations that weight gain of the Fgf13 +/2 mice was almost all fat mass and that there was no difference in the lean mass of the WT and Fgf13 +/2 mice and because it has been shown that from 13 to 17 wk, the majority of weight gain in female C57BL/6J mice is fat mass (34). Using these parameters, we extrapolated the change in weight to 16 wk of age by multiplying the daily fat gain by the number of days.…”
Section: Metabolic Measurement and Data Analysismentioning
confidence: 99%
“…We compared theFgf13 +/2 mice's daily EE (previously corrected by ANCOVA for LBM, with that of WT mice and converted the deficit to grams by dividing by the caloric content of fat to obtain a predicted fat gain per day. We used the caloric content of fat because of the observations that weight gain of the Fgf13 +/2 mice was almost all fat mass and that there was no difference in the lean mass of the WT and Fgf13 +/2 mice and because it has been shown that from 13 to 17 wk, the majority of weight gain in female C57BL/6J mice is fat mass (34). Using these parameters, we extrapolated the change in weight to 16 wk of age by multiplying the daily fat gain by the number of days.…”
Section: Metabolic Measurement and Data Analysismentioning
confidence: 99%
“…After acquisition, 3D reconstructions were performed using the Rigaku software and morphometric analyses were performed using the OsiriX imaging software (v.5.6 64 bit; OsiriX, Geneva, Switzerland) from stacks of 2D images. Body mass index (BMI) was calculated by dividing the weight (in g) by the square root of the tail‐less length (in cm), and body surface was calculated by dividing the tail‐less length (in cm) by the cube root of the weight (in g), as described …”
Section: Methodsmentioning
confidence: 99%
“…Body mass index (BMI) was calculated by dividing the weight (in g) by the square root of the tail-less length (in cm), and body surface was calculated by dividing the tail-less length (in cm) by the cube root of the weight (in g), as described. (34) Hormonal and biochemical measurements in plasma and urine Plasma and urinary calcium, phosphorus, and creatinine were determined using a Modular P Roche analyzer. Plasma intact PTH and thyroid-stimulating hormone (TSH) were measured by ELISA (Immutopics, San Clemente, CA, USA and Cloud-Clone Corp, Houston, TX, USA, respectively).…”
Section: Histomorphometrymentioning
confidence: 99%
“…Indeed, profound abnormalities in brain structural and functional development due to social isolation occur specifically during adolescence, disrupting cognitive and behavioural function at later life stages (2224). Adolescence is also a period of rapid lean body growth (25), which is accompanied by a high energy demand. Moreover, this period also represents a critical phase for the development and maturation of (visceral) white adipose tissue (26–28) and the structural and functional maturation of the hypothalamic circuits that control food intake (29).…”
Section: Introductionmentioning
confidence: 99%